1976
DOI: 10.1007/bf01065725
|View full text |Cite
|
Sign up to set email alerts
|

Selection for agonistic behavior in wild femaleMus musculus

Abstract: Artificial selection was used to establish different levels of agonistic behavior in laboratory-reared wild female Mus musculus. A within-family selection design with replicated high and low lines and two nonselected control lines was employed. Females only were tested at 8 weeks of age on 2 consecutive days. Testing consisted of placing a C57BL/6 female mouse in the home cage of the isolation-reared wild mouse for 7 min or until an attack occurred. The wild females were rated on a 5-point scale for agonistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…These differences can be caused by both environmental and genetic factors. Mouse strains can differ substantially in their levels of aggressive behavior (Ginsberg and Allee, 1942; Scott, 1942), and selective breeding on a certain aspect of aggressive behavior has successfully produced strains of mice that exhibit high and low levels of aggression (Lagerspetz, 1964; Ebert and Hyde, 1976; van Oortmerssen and Bakker, 1981; Gariepy et al, 1996; Sandnabba, 1996). The identification of several knockout mice that show either increased or decreased aggressive behaviors (for reviews, see Miczek et al, 2001; Nelson and Chiavegatto, 2001; Takahashi et al, 2012) indicates that many genes affect aggression.…”
Section: Introductionmentioning
confidence: 99%
“…These differences can be caused by both environmental and genetic factors. Mouse strains can differ substantially in their levels of aggressive behavior (Ginsberg and Allee, 1942; Scott, 1942), and selective breeding on a certain aspect of aggressive behavior has successfully produced strains of mice that exhibit high and low levels of aggression (Lagerspetz, 1964; Ebert and Hyde, 1976; van Oortmerssen and Bakker, 1981; Gariepy et al, 1996; Sandnabba, 1996). The identification of several knockout mice that show either increased or decreased aggressive behaviors (for reviews, see Miczek et al, 2001; Nelson and Chiavegatto, 2001; Takahashi et al, 2012) indicates that many genes affect aggression.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal aggression in defense of pups dominates this literature (4,16,17), but isolation-induced and territorial female aggression has been reported and characterized also (5)(6)(7)(8). In laboratory-reared wild populations of female mice, isolation-induced spontaneous aggression was found to be a selectable trait (18). Careful comparative studies have revealed that similar amine, steroid, and peptide hormones modulate aggression in both males and females, and in some cases, parallel changes have been seen in hormone usage in males and females during aggressive interactions (4,19).…”
mentioning
confidence: 99%
“…On the other hand, C3H males (experiment 11) are more aggressive against strangers than against cagemates (residents) of the same strain, a phenomenon that has been described many times in small rodents [Rowe et al, 1969;Poole and Morgan, 19751. Little support for the notion that this effect of familiarisation is linked t o the perception of olfactory stimuli, or, if it is (as suggested by Mackintosh and Grant [ 19661 ), that a positive correlation exists between the aggression of males and that of females [Hyde and Ebert, 1976;Ebert and Hyde, 19761 is evident in the literature so this seems an unlikely possibility.…”
Section: C) the Three Strains Of Mice Do Not Have The Same Olfactory mentioning
confidence: 88%